2017
DOI: 10.3758/s13414-017-1426-2
|View full text |Cite
|
Sign up to set email alerts
|

Processing of haptic texture information over sequential exploration movements

Abstract: Where textures are defined by repetitive small spatial structures, exploration covering a greater extent will lead to signal repetition. We investigated how sensory estimates derived from these signals are integrated. In Experiment 1, participants stroked with the index finger one to eight times across two virtual gratings. Half of the participants discriminated according to ridge amplitude, the other half according to ridge spatial period. In both tasks, just noticeable differences (JNDs) decreased with an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 56 publications
6
29
0
Order By: Relevance
“…In our experiments, we showed that when participants adjusted their peak force more precisely to the object they also generated more sensory signals. In previous work, we additionally showed that perception gets more precise with more generated sensory signals (Lezkan and Drewing, 2018 ; Metzger et al, 2018 ). In sum, accumulating sensory signals seems to improve the precision of movement and perception.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…In our experiments, we showed that when participants adjusted their peak force more precisely to the object they also generated more sensory signals. In previous work, we additionally showed that perception gets more precise with more generated sensory signals (Lezkan and Drewing, 2018 ; Metzger et al, 2018 ). In sum, accumulating sensory signals seems to improve the precision of movement and perception.…”
Section: Discussionmentioning
confidence: 54%
“…Consequently, it may be that in our experiment, the reliability of sensory information was not sufficient to warrant a significant effect on movement control. In active touch, sensory information gains reliability with extension of exploration; the more movements performed, the more sensory signals are generated, and the more reliable the sensory information overall will be (Lezkan and Drewing, 2018 ). Therefore, it seems possible that our participants did not explore with the necessary extension to generate sufficient sensory signals.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In haptic perception it was shown that prior information is integrated into the percept of an object's softness [15]. It was also shown that sequentially gathered information from every indentation contributes to the overall perception of an object's softness [16] and information from every stroke over the object's surface contributes to the perception of its roughness [17]. However, the contribution of these single exploratory movements to the overall percept seems to be not equal, as would be predicted if there was no loss of information and integration was statistically optimal.…”
Section: Introductionmentioning
confidence: 99%